Role of Radiology in Diagnosis of Allergic Fungal Sinusitis - Jamil, Nauman; Jahangir Ahmad Afridi; Muhammad Khan; Kamran Zamurrad Malik; Faisal Manzoor; Bhalli, Naeem Riaz (Pakistan Armed Forces Medical Journal, 2024)
Objective: Investigate the role of serrated turbinates, radiographic abnormalities, and existing literature in aiding the diagnosis of Allergic Fungal Sinusitis (AFS). Study Design: Cross-sectional study Place and Duration of Study: ENT Department Combined Military Hospital, Rawalpindi, Pakistan from Jan 2020 to July 2023. Methodology: One hundred and twenty individuals with computerized tomography scans were included. Patients identified as having Allergic Fungal Sinusitis (AFS) following tests for allergies and/or fungi were placed in the first group, while those identified as having rhinosinusitis (other than AFS) were placed in the second group. CT scans were examined for polyps, bone degradation, the serrated appearance of the turbinate, and CT hyper-density. Results: While comparing the radiology of AFS and non-AFS, it was discovered that the presence of serrated turbinate was prevalent in AFS (p<0.05), with no differences in terms of bone degradation, polyps, or CT hyper-density (p>0.05). The mean age was 36.81±11.24 years. There were 120 patients; 86(72%) were AFS (-ve), and 34(28%) were AFS (+ve) individuals. Out of them, 19(16%) of the AFS (+ve) patients were females, whereas 15(12%) were males. Conclusion: Serrated turbinates may serve as helpful radiological signals in the diagnosis of AFS. For assessing bone erosion in relation to other structural changes, it is important to specify bone density for sinus opacification.